KEMAMPUAN USAHA DAN PEMANFAATAN TEKNOLOGI INFORMASI UNTUK MENCAPAI KEBERHASILAN USAHA AYAM GEPREK DI KOTA MATARAM - Animah, Animah; Astuti, Widia; Nabila, Dende Tialurra Della (Universitas Muhammadiyah Jember, 2024)
This research aims to empirically test the influence of business capabilities and the use of information technology to achieve success in the Geprek Chicken business in Mataram City. The population in this study is 141 culinary MSMEs that have registered with the go food service and use chicken meat as their processed product. The sample used was 72 MSMEs which were determined based on the sampling technique, namely purposive sampling. The analysis technique used in this research is the SEM-PLS (Structural Equation Modeling-Partial Least Square) analysis technique. The results of this research show that business capabilities and information technology influence business success. The implications for MSMEs are that by using information technology and balancing it with the ability to manage the business, it will increase business success. Future researchers can add the variables of continuous improvement and financial literacy.